Patient with Lynch syndrome with subsequent development of small bowel adenocarcinoma. (4th June 2018) - Azizi, Abdul Hussain; Inam, Zaina S; Farrell, Timothy J
Abstract : Small bowel adenocarcinoma (SBA) is a rare cancer in the general population, but the incidence increases in patients with Lynch syndrome. The present case describes a 57-year-old white woman with a history of colon cancer status posthemicolectomy and diagnosis of Lynch syndrome. Twenty years after her operation, the patient presented with vague abdominal discomfort and constipation, and underwent an exploratory laparotomy which revealed a stage 3A SBA. Genetic testing of the specimen provided evidence of microsatellite instability and faulty DNA repair supporting aetiology of Lynch syndrome. This case is unique in that SBA, if present in patients with Lynch syndrome, is usually a presenting symptom and has not been widely described in literature as an occurrence so many years after. As a result, this case highlights the importance of a low threshold for a thorough evaluation in patients with Lynch syndrome who present with signs of small bowel obstruction.